2018
DOI: 10.18203/2319-2003.ijbcp20181181
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heparin prescription before primary PCI on long-term and short-term clinical and para clinical results and the mortality of patients with acute coronary syndrome

Abstract: INTRODUCTIONCoronary artery disease (CAD) is the main cause of death, morbidity and disability in the world and their prevalence is highly increasing in developing countries. In CAD patients, acute coronary syndrome (ACS) has the most importance because of the high possibility of unpleasant cardiovascular events during follow-up was more in these patients. In 2008, 7.3 million (12.8%) out of 57 million deaths was because of myocardial infraction. In the United States, almost 650 thousand patients get new acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
(22 reference statements)
1
2
1
Order By: Relevance
“…12 Conversely, Zamani and colleagues demonstrated that there were no differences between TIMI scores in two groups. 9 Four major bleeding occurred in the current study, 3 (1.5%) in the heparin group and 1 (0.5%) in the control group, which is not significantly higher than previous studies that heparin be prescribed with PCI. [10][11][12][13][14] Of these 4 patients, all experienced profuse bleeding in the tracheostomy site, and 2 patients required a blood transfusion after PCI.…”
Section: Comparison Of This Results With Other Studiescontrasting
confidence: 66%
See 3 more Smart Citations
“…12 Conversely, Zamani and colleagues demonstrated that there were no differences between TIMI scores in two groups. 9 Four major bleeding occurred in the current study, 3 (1.5%) in the heparin group and 1 (0.5%) in the control group, which is not significantly higher than previous studies that heparin be prescribed with PCI. [10][11][12][13][14] Of these 4 patients, all experienced profuse bleeding in the tracheostomy site, and 2 patients required a blood transfusion after PCI.…”
Section: Comparison Of This Results With Other Studiescontrasting
confidence: 66%
“…Zamani and colleagues reported that in case group compared to control group the rate of hematoma was higher but not significant. 9 Plus, Bonello's survey in USA, with a similar design as ours, found that the incidence rate of Hematoma in heparin group was more than control group. 16 The findings of this study showed that the control group had more 30-day death compared to intervention group but difference was not statistically significant (1.5% vs. 0%).…”
Section: Comparison Of This Results With Other Studiessupporting
confidence: 65%
See 2 more Smart Citations